Adaptive immunity and IL‐17A are not involved in the progression of chronic kidney disease after 5/6 nephrectomy in mice. (18th December 2018) - Rosendahl, Alva; Kabiri, Reza; Bode, Marlies; Cai, Anna; Klinge, Stefanie; Ehmke, Heimo; Mittrücker, Hans‐Willi; Wenzel, Ulrich O
Abstract : Background and Purpose: The adaptive immune response and IL‐17A contribute to renal damage in several experimental models of renal injury. Experimental Approach: To evaluate the role of the adaptive immune response, 5/6 nephrectomy was performed in wildtype DBA/1J mice and in recombination‐activating gene‐1 (RAG‐1) deficient mice that lack B and T‐cells. To assess the role of IL‐17A, we carried out 5/6 nephrectomy in IL‐17A deficient mice. Flow cytometric analysis, immunohistochemistry and RT‐PCR were used. Key Results: Infiltration of CD3 + T‐cells in the remnant kidney was increased after 5/6 nephrectomy in wildtype mice, along with a robust induction of IL‐17A production in CD4 + T and γδ T‐cells. After 5/6 nephrectomy, wildtype mice developed albuminuria in the nephrotic range over 10 weeks. This was accompanied by severe glomerular sclerosis and tubulointerstitial injury, and as well as renal mRNA expression of markers of inflammation and fibrosis (the chemokine CCL2, plasminogen activator inhibitor‐1; PAI‐1 and neutrophil gelatinase‐associated lipocalin; NGAL). Unexpectedly, RAG‐1 deficient mice and IL‐17A deficient mice developed renal injury, similar to that in wildtype mice. No differences were found for albuminuria, glomerular sclerosis, tubulointerstitial injury and mRNA expression of CCL2, PAI‐1 and NGAL. Mortality did not differ between the three groups. Conclusions and Implications: Numbers of CD3 + T‐cells and IL‐17A + lymphocytes infiltrating the kidney were increased after 5/6 nephrectomy. In contrast to other experimental models of renal injury, genetic deficiency of the adaptive immune system or of IL‐17A did not attenuate induction or progression of chronic kidney disease after 5/6 nephrectomy. Linked Articles: This article is part of a themed section on Immune Targets in Hypertension. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.12/issuetoc